Pengembangan Onlineshop di Kalangan Masyarakat Menengah Kebawah Di Baloi Indah, Kecamatan Lubuk Baja, Kelurahan Baloi Indah, Batam - Darwinto, Vicky; Rino, Rino; Tan, Nelson; Agung, Hakim; Qaadir, Qaadir; Alvita, Wini; Fernando, Rizky; Ong, Milenia; Armando, Jose (National Conference for Community Service Project (NaCosPro), 2019)
A program aimed in order to improve and increase their economy by using a Dropship/Online shop and to additional income for the housewife to help their husband to raise their family and so in the future they can offer job vacancy.